Sosialisasi Penggunaan Pupuk bioorganik-fosfat Pada Tanaman Cabai Merah (Capsicum annum L) - Lolita Endang Susilowati; Zaenal Arifin (Jurnal Gema Ngabdi, 2020)
Bioorganic-phosphate fertilizer is an organic fertilizer enriched with phosphate solubilizing rhizobacteria (PSR). The addition of PSR to organic fertilizers is intended to improve the quality of organic fertilizer. The purpose of this community service activity is to socialize the use of bioorganic-phosphate fertilizers on red chili plants for reducing the use of inorganic fertilizers. This service activity used a participatory approach. As a target farmer partner is the "Bahtera" farmer group in Narmada Village, Narmada District, West Lombok Regency. This activity began with establishing a joint agreement between the community service team and the target farmers through a group discussion (FGD). The next activity was an extension activity about "bioorganic-phosphate fertilizer, its role, and benefits". Next, Activity of demonstration plot of integrated fertilizing was made at the farmer land to show the difference in yield with/ without used the combination fertilizer of bioorganic-phosphate and inorganic fertilizer. The chili yields show that fertilizing of the combination of bioorganic-phosphate and 75% of the recommended fertilizer dosage is higher than the 100%  of the recommended dose. these community service activities achieve a positive response from farmers.  This socialization activity needs to be carried out in other locations so that more farmers applying a fertilization pattern by combining bioorganic-phosphate and inorganic fertilizers